Metode Penelitian Kepustakaan dalam Pendidikan Islam - Abdurrahman (Adabuna : Jurnal Pemikiran dan Pendidikan, 2024)
Library research is a significant method in Islamic education to examine various written sources. This paper discusses the definition, objectives, advantages and disadvantages, data sources, characteristics, types, stages, and benefits of library research in Islamic education. The objectives of library research are to build understanding, identify perspectives, analyze knowledge gaps, develop theoretical frameworks, formulate research questions, analyze data, draw conclusions, and develop new theories. Data sources are diverse, including books, journals, documents, online databases, and special collections. Library research has the characteristics of being qualitative, descriptive, non-fieldwork, and emphasizing the researcher's role in data analysis. Types of library research are classified based on purpose and data type. Based on purpose, it can be categorized as historical, descriptive, explanatory, and evaluative research. Based on the type of data, it can be categorized as historical, philosophical, or comparative research. The stages of library research include determining the topic, searching for data, analyzing data, organizing data, and writing a report. Library research has many benefits in Islamic education, such as building theoretical foundations, identifying knowledge gaps, understanding the history and development of Islamic education, studying the theory and philosophy of Islamic education, and improving PAI teaching strategies.